Pipeline vantage embolization device for the treatment of intracranial aneurysms: a systematic review and meta-analysis - Görtz, Lukas; Hohenstatt, Sophia; Zopfs, David; Kottlors, Jonathan; Pennig, Lenhard; Schlamann, Marc; Michael, Arwed Elias; Liebig, Thomas; Möhlenbruch, Markus Alfred; Kabbasch, Christoph (Interventional neuroradiology, 2024)
Objective - The Pipeline Vantage Embolization Device (PVED) is a novel coated flow diverter with reduced wire diameters to improve neoendothelialization and stent porosity. This systematic review evaluates the safety and efficacy of the PVED based on the current literature. - Methods - Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, a thorough literature search was conducted using PubMed, EMBASE, and Cochrane. The random effects model was used to calculate estimates with major neurological complications within 30 days of treatment as the primary safety endpoint and ≤1-year complete occlusion rate as the primary efficacy endpoint. - Results - Six single-arm studies (5 retrospective, 1 prospective) with 392 patients and 439 aneurysms (6.8% ruptured) were included. Antiplatelet regimens varied, but dual antiplatelet therapy was administered in the majority. The pooled technical success rate was 99.0% (95%CI, 98.0%-100%) with an average of 1.2 devices implanted per procedure. Balloon angioplasty was performed in 17.0% (95%CI, 6.4-27.6%) and adjunctive coiling in 28.0% (95%CI, 17.8-38.2%), with significant heterogeneity for both variables. Pooled estimates for major neurological complications were 3.5% (95%CI, 1.7%-5.2%) with total ischemic events in 4.1% (95% CI, 1.6%-6.6%) and hemorrhagic events in 1.0% (95% CI, 0.0%-1.9%). The rate of complete angiographic occlusion was 75.7% (95%CI, 70.7%-80.6%) at a mean follow-up of 7 months, with in-stent stenoses in 8.1% (95%CI, 4.5%-11.8%). - Conclusions - The safety and efficacy profile of the PVED appears comparable to competing devices, with potentially fewer complications than first-generation flow diverters. Long-term and comparative studies are needed to further confirm these results.